ANALISIS HUTANG LUAR NEGERI INDONESIA PENDEKATAN KESEIMBANGAN MAKROEKONOMI - Imamudin Yuliadi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
There are so many interesting phenopenon if we discuss of Indonesian economy especially at monetary sector. Foreign debt is one of several popular problem on developing countries like Indonesia. It is one of practice solution about saving debt to maintain the development process. The aim of this research is to analyse some factors that affect foreign debt and their implications on Indonesian economy. Analytical method used in this research is explanatory method is to test hyphotesis about simultaneous relationship among variables that research by developing the characteristics of verificative research by doing some testing at every step of research. We used secondary data taken from BI, BPS, World Bank and IFS. The result of this research shows that ratio between domestic interest rate and international interest rate, government expenditure and national income did not affect significantly to foreign debt. Exchange rate affected positive and significantly to foreign debt